THE IMPLEMENTATION OF REALIA AND DIGITAL MEDIA IN THE FORMING OF STUDENTS’ CHARACTER IN SKI SUBJECTS AT SMAN 1 MAGETAN - Nikmah, Faridatun; Aminah, Siti; Bisri, Kasan (Proceeding of International Conference on Islamic Education (ICIED), 2022)
Islamic Cultural History (SKI) is one of the subjects that must be understood by students in Islamic-based educational institutions. If in public schools the SKI subject is integrated into the PAI subject. To achieve maximum understanding, appropriate methods and media are needed. Using the realia and digital media is an option in an effort to build student character in SKI subjects. The research method used a qualitative approach, namely the data obtained through observation, interviews and literature studies. The results of the study explain that the use of both realia and digital media, or mixed learning media (blended learning media) is able to contribute the forming of students’ character. Precisely, through ibrah/messages that can be taken from the SKI materials that have been delivered by an interesting learning media.